Teachers' Coping Strategies and Job Satisfaction in Distance Teaching During the COVID-19 Pandemic - V.A. Manina; A.V. Petrakova; A.A. Kulikova; E.A. Orel; T.N. Kanonire (Moscow State University of Psychology and Education, 2023)
The article presents the results of an empirical study, which aims to analyze the relationships between teachers’ coping strategies and job satisfaction in distance teaching during the COVID-19 pandemic. The study sample consisted of primary school teachers from two large regions in Russia (N=313). The main method was a survey. The questionnaire included the following topics: respondents’ demographic information, coping strategies, job satisfaction, technical tools used for distance learning, forms of school administration support, learning events for teachers, as well as applied practices. The results of the logistic regression analysis showed that there is a positive relationship between using productive coping strategies and job satisfaction. It was also determined that the relationship between job satisfaction and some factors such as school administration support and the possibility of applying new practices.